PROFILE OF SUBJECTIVE SLEEP DISTURBANCE IN PATIENT WITH ANTIEPILEPTIC DRUGS - Zahra, Farah Az; Islamiyah, Wardah Rahmatul; Budiono, Budiono (Malang Neurology Journal, 2019)
Background: Epilepsy and sleep are well recognized for having bidirectional influences upon one another. The effects of antiepileptic drugs (AEDs) on sleep are of particular concern. Objective: The objective of this study is to know the profile of AEDs effect in patient’s sleep cycle. Methods: This analytical observational study observed total sleep time, sleep onset latency, sleep efficiency, daytime sleepiness, and insomnia in epileptic patient with AEDs of Neurology Clinic Airlangga University Hospital during May-September 2016. A cross sectional study was done by questionnaire and interview directly to the epileptic patients. Data collected was being analyzed analytically.Results: This research was conducted among 27 patients with epilepsy based on inclusion and exclusion criteria. Sleep disturbances that had been found in patients with phenytoin are prolong sleep onset latency (11.11%), decreased sleep efficiency (11.11%), and excessive daytime sleepiness (66.67%). Sleep disturbances that had been found in patients with valproate are decreased total sleep time (33.33%), prolong sleep onset latency (11.11%), decreased sleep efficiency (11.11%), excessive daytime sleepiness (66.67%), and insomnia (11.11%). Sleep disturbances that had been found in patients with carbamazepine are decreased total sleep time (44.44%), prolong sleep onset latency (33.33%), decreased sleep efficiency (22.22%), excessive daytime sleepiness (77.78%), and insomnia (11.11%).Conclusion: In conclusion, this study shows that epileptic patients who consumed AEDs regularly may have sleep disturbance that vary based on the type of AEDs, patients with carbamazepine may have bigger sleep disturbance than with phenytoin and valproate. It is necessary to give information and education to the epileptic patients who consumed AEDs regularly so that they will become aware of the sign of sleep disturbance.